To not love thy neighbor: mechanisms of cell competition in stem cells and beyond. - Yusupova, M.; Fuchs, Y. (Cell Death and Differentiation, 2023)
Cell competition describes the process in which cells of greater fitness are capable of sensing and instructing elimination of lesser fit mutant cells. Since its discovery in Drosophila, cell competition has been established as a critical regulator of organismal development, homeostasis, and disease progression. It is therefore unsurprising that stem cells (SCs), which are central to these processes, harness cell competition to remove aberrant cells and preserve tissue integrity. Here, we describe pioneering studies of cell competition across a variety of cellular contexts and organisms, with the ultimate goal of better understanding competition in mammalian SCs. Furthermore, we explore the modes through which SC competition takes place and how this facilitates normal cellular function or contributes to pathological states. Finally, we discuss how understanding of this critical phenomenon will enable targeting of SC-driven processes, including regeneration and tumor progression.